Gestión de comercialización del Taller de Pintura Automotriz de Jonathan en el periodo 2022 - Carrillo Bravo, Jonathan José (2023)
In recent years, the establishment of TALLER DE PINTURA AUTOMOTRIZ DE JONATHAN has experienced a significant decline in its position in the Babahoyo automotive market, with a constant decrease in sales being its main challenge. The purpose of this research is to identify the reasons behind the ongoing loss of the company's position, which was addressed through a descriptive and field-based approach. Surveys were conducted with customers, and interviews were carried out with the General Manager of the company, as well as experts in relevant areas such as marketing and the automotive market. The data obtained, expressed both qualitatively and quantitatively, led to the conclusion that the lack of marketing strategies, absence of promotions, and deficiencies in the business infrastructure are the main underlying causes of the problem. As a result, a proposal was developed that involves creating a marketing plan encompassing strategies related to price, product, distribution, and promotion. The aim is to foster loyalty among current customers of TALLER DE PINTURA AUTOMOTRIZ DE JONATHAN and attracts new clients. This initiative seeks to increase sales and generate higher revenues for the company. Discounts, packages, coupons, giveaways, the use of social media, and closer customer engagement are some of the proposed measures to revitalize the workshop's position in the market.